Acoustic spectra processing for the determination of cavitation threshold in a high-frequency sonoreactor in water and PEG mixtures from 1 to 54 mPa.s - V. Avramovic; L. Hallez; C. Inserra; J-Y Hihn (Ultrasonics Sonochemistry)
Ultrasound-induced cavitation, especially its stable and inertial regimes, plays a critical role in sonochemical processes. Thus, finding the power thresholds differentiating the appearance of stable cavitation and then transient cavitation, is essential for sonoreactor characterization since this knowledge allows the relevant choice of operating parameters leading to the expected sonochemical effects. However, this concept is difficult to grasp and often applied with complex techniques difficult to implement and highly “system dependent”. The study of sonochemical activity and efficiency in a high frequency reactor (575 kHz) provides an opportunity to take an interest in the step-by-step implementation of a hydrophone measurement, from selection of the device to recording procedures, and especially signal processing with selection and extraction of the two most relevant probes: 3F0/2 magnitudes useful for detecting stable cavitation and cumulative integration of broadband noise and its interpretation (slope discontinuity) to get an indication of transient cavitation appearance. An original result of this work is that this technique appears to be much more reliable and sensitive than chemical techniques when media are very viscous, remaining relevant beyond the limits of sonochemiluminescence and dosimetry techniques. This is interesting because it makes it possible to link evolution of the change thresholds of cavitation state (from absence of cavitation to stable cavitation, then transient cavitation) with an increase in viscosity. As expected, these thresholds increase, from 0.25 W- stable cavitation − and 2 W – inertial cavitation − in water up to 6 W for stable cavitation and an absence of inertial cavitation at 54 mPa.s, as it is necessary to apply more power to achieve cavitation in high viscous media. This range of magnitude of viscosity used in this study is relevant for specific applications, such as ultrasonic cleaning lines involving cleaning solutions and all scientific issues dealing with deep eutectic solvants (DES) for electropolishing or leaching processes in metal recovery. A constant monitoring by measuring regularly these parameters ensures that cleaning or treatment lines are running at constant efficiency and helps to identify critical breakdowns. Finally, what is remarkable is that the stable cavitation threshold seems to be directly proportional to the acoustic field (linear dependence of the stable cavitation threshold) if the latter is expressed in pressure, providing new challenges for acoustic fields modelling.